Correlation Between FNAC and Open Biopsy in Cervical Lymhadenopathy in Children (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Head and Neck region of the body has a rich network of lymphatic channel and intervening nodes. Out of total approximately 800 lymph nodes in the body about 300 are scattered in organized fashion in the neck region which are affected by various regional and systemic diseases. The conventional method of excisional biopsy is used to diagnose etiological causes of lymphadenopathy. In comparison to open surgical biopsy, FNAC is a simple, reliable and acceptable tool for the etiological diagnosis of lymphadenopathies. FNAC was first practiced by Grieg and Gray for the diagnosis of trypanosome in lymphnode in 1904. Now a day it is widely practiced in United States, United Kingdom and many other countries. In Bangladesh, many studies on FNAC are carried out and the results are highly appreciable and reliable.Methods: A prospective study for a period of 24 months was carried out on 50 patients with enlarged cervical lymph nodes from July 2003 to June 2005. During the two years study period, 56 patients with cervical lymphadenopathies were selected for FNAC and openbiopsy following certain inclusion and exclusion criteria, in the Department of Pediatric Surgery, Bangabandhu Sheikh Mujiib Medical University, Dhaka. Patients with acute lymphadenitis and lymphadenopathy due to leukaemia were excluded. Six cases were deleted from the study as smears from those revealed inadequate material and hence only 50 cases were available for study in the present series. Clinical findings, FNAC and biopsy reports were available in all the cases and were correlated with each other.Results: On biopsy, 27 cases were diagnosed as tuberculous lymphadenopathies, 15 cases as lymphoma and 8 cases as reactive changes. On FNAC, there were 2 false positive and 5 false negative cases in case of tuberculosis; 2 false positive and 1 false negative cases in lymphoma; 4 false positive and 2 false negative cases in cases with reactive hyperplasia. Sensitivity of FNAC in comparison to histopathological findings was 92.6% in case of tuberculosis; 86.7% in case of lymphoma and 50% in case of nonspecific lymphadenitis. Specificity of FNAC in comparison to histological findings was 78.3% in case of tuberculosis; 94.2% in case of lymphoma and 95.3% in case of nonspecific lymphadenitis. Accuracy of FNAC in comparison to histopathological findings was 86% in case of tuberculosis; 94% in case of lymphoma and 88% in case of reactive changes.Conclusions: The present study indicates that, FNAC is a simple, reliable and acceptable procedure for various lesions of cervical lymph nodes. It can be repeated if necessary. It also concludes that FNAC helps to confirm the clinical impression without open biopsy. Open biopsy can be avoided in many benign and malignant lesions of cervical lymph nodes. Fine needle aspiration cytodiagnosis can eliminate the need of hospitalization and surgery.DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19526